2008
DOI: 10.1177/0898264308321025
|View full text |Cite
|
Sign up to set email alerts
|

Social Care Interface in Early-Stage Dementia

Abstract: The problematic interface between formal and informal service networks could be improved by a greater understanding of microsocial- and organizational-level interactions and implementing a social model of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Another topic of research focuses on the collaboration between caregivers and professionals. Studies show that caregivers are not always satisfied with their collaboration with professionals (Carpentier, Pomey, Contreras, & Olazabal, 2008;McPherson, Kayes, Moloczij, & Cummins, 2013;Ward-Griffin & McKeever, 2000;Zwart-Olde, Jacobs, Broese van Groenou, & van Wieringen, 2013). Having a shared meaning of the relationship and the situation is important in order to achieve a good collaboration.…”
mentioning
confidence: 99%
“…Another topic of research focuses on the collaboration between caregivers and professionals. Studies show that caregivers are not always satisfied with their collaboration with professionals (Carpentier, Pomey, Contreras, & Olazabal, 2008;McPherson, Kayes, Moloczij, & Cummins, 2013;Ward-Griffin & McKeever, 2000;Zwart-Olde, Jacobs, Broese van Groenou, & van Wieringen, 2013). Having a shared meaning of the relationship and the situation is important in order to achieve a good collaboration.…”
mentioning
confidence: 99%
“…A detailed description of the relevant studies is summarized in Table 3. One strength of the 6 studies reviewed above was that 4 of these studies were based on theoretical models [26, 28-30]. Further, all of the selected studies reported statistically significant results, revealing significant associations between “social networks” or “social interaction” and QoL, meaning, and positive interactions among PWD and their caregivers.…”
Section: Resultsmentioning
confidence: 99%
“…Carpentier et al [26] highlighted the importance of professionals and informal caregivers considering service integration. If there is a lack of coordination between institutions and family caregivers, the quality of care delivered to PWD may be compromised [47].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their analysis of the "interface" between formal and informal service networks in earlystage dementia care, Carpentier et al (2008) adopt a "multilevel network model", which considers "family systems and community groups as well as professional establishments". Pickens (2003) uses the same interface in relation to care for women with serious mental illness, yielding the recommendation that each client's context be recognized "apart from his or her illness", and that it is important to capitalize on positive factors within the client's life as means to foster network building.…”
Section: Weak Formal Networkmentioning
confidence: 99%